Impact of COVID-19 on Utilisation of Funds by People With Disabilities: Lessons Drawn From the Australian National Disability Insurance Scheme - Yu Zhang; Satish Chand (Kerman University of Medical Sciences, 2023)
Background  COVID-19 pandemic has affected everyone, especially people with disabilities (PwD). While there has been qualitative research on the impact of the pandemic on PwD in Australia, little quantitative evidence has been produced on the magnitude of this impact.Methods  A range of descriptive analytic methods are employed on the data merged from the National Disability Insurance Scheme (NDIS) and COVID-19 data on national, state, and regional levels to compare the expenditure of the NDIS participants who are in pandemic-affected regions and time periods with those that are not. Regression analysis is also performed to estimate the participants' utilisation of funds using explanatory variables drawn from the NDIS, COVID-19, and lockdown policy information.Results  Our analysis reveals that: (1) the pandemic reduced expenditure of the NDIS participants by approximately A$ 31.2 million, equal to 8.85% of the total expenditure over five quarters for the state of Victoria (VIC) alone; (2) the contractions in expenditure lasted for up to two quarters during the pandemic; (3) the reductions in expenditure were largely associated with the limited mobility imposed via lockdowns compared to the impaired access to services; and (4) the spread of COVID-19 that led to restrictions on mobility of people had a bearing on utilisation of funds by NDIS participants in the subsequent quarter.Conclusion  COVID-19 has affected the expenditure of the PwD in Australia. We overlaid the NDIS data on the COVID-19 outbreaks to estimate the impact of the pandemic on expenditure and utilisation rate of the funds allocated to the NDIS participants. Our findings point to potential policy interventions to mitigate some of the adverse consequences of similar nationwide emergencies.